PENGARUH METODE SAS UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 1 SD - Audisa Shafa Indira Rahman audi; Ramanata Disurya; Farizal Imansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of the SAS method to improve the reading ability of first grade elementary school students. The research method used is a quantitative type of experiment in the form of a pre experimental design and a one group pretest posttest design. The population in this study amounted to 21 first grade elementary school students. The sample in this study used a purposive sampling technique. Data collection techniques used are observation and tests. The data analysis technique used is the t test (paired sample t-test). From the results of research data processing with the help of the SPSS 26 application, the value of ????ℎ???????????????????? = 8.302 ≥ ???????????????????????? = 1.725 with α = 0.05 and df = 20, then 8.302 ≥ 1.725 thus ????ℎ???????????????????? ≥ ????????????????????????. In accordance with the prerequisites for testing the hypothesis, ????0 is rejected and ???????? is accepted or there is a significant effect between the Synthetic Structural Analytical (SAS) method to improve the reading ability of class I elementary school students.